High dynamic range vector soliton mode-locking via nonlinear Sagnac gating - Kun Chen; Tao Cao; Xinyi Yan; Jinlong Zheng; Zhou Li; Qi Xu; Leyan Yang; Jing Li; Mingtao Peng; Yuxin Leng; Jiahui Peng (APL Photonics)
Ultrafast fiber lasers enable vector soliton generation with richer dynamics than scalar solitons, offering enhanced flexibility for high-capacity communications and optical storage. However, generating vector solitons in short resonators without any physical saturable absorbers remains challenging, consequently limiting their dynamic ranges, energy scales, and repetition rates. Here, we propose a nonlinear Sagnac gating method in a hybrid mode-locked fiber laser to facilitate intracavity vector soliton generation, combining nonlinear amplifying loop mirror and nonlinear polarization rotation (NPR) mechanisms. This method significantly enhances the vectorial characteristics of solitons within a single short round trip, enabling high-repetition-rate operation even with the intracavity polarizer necessary for NPR. In turn, pulse shaping and phase bias introduced by NPR effectively improve system stability and reduce the self-starting mode-locking threshold. The expanded parameter space and dynamic range enable flexible switching between various vector soliton states. Moreover, the polarization states on the generated vector solitons no longer change pulse by pulse, ready for scientific and industrial applications. Our research results offer valuable insights into the formation and evolution of vector solitons. The developed laser also provides an excellent multifunctional platform for simulating complex nonlinear systems and investigating the corresponding soliton dynamics.